GnRH Agonist and hCG (Dual Trigger) Versus hCG Trigger for Final Oocyte Maturation in Expected Normal Responders With a High Immature Oocyte Rate: Study Protocol for a Randomized, Superiority, Parallel Group, Controlled Trial - Yan, Meng-Han; Cao, Jing-Xian; Hou, Jin-Wei; Jiang, Wen-Jing; Wang, Dan-Dan; Sun, Zhen-Gao; Song, Jing-Yan (Frontiers in Endocrinology, 2022)
Introduction The choice of trigger drug for the controlled ovarian hyperstimulation (COH) protocol correlates with the outcome of in vitro fertilization/intracytoplasmic sperm injection embryo transfer (IVF/ICSI-ET). The co-administration of gonadotropin releasing hormone agonist (GnRH-a) and human chorionic gonadotropin (hCG), i.e., dual trigger, for final oocyte maturation, has received much attention in recent years. This trial was designed to determine whether a dual trigger approach by lengthening the time between trigger and ovum pick-up (OPU) improves the quantity and quality of mature oocytes/top-quality embryos and pregnancy outcomes in expected normal responders with a high immature oocyte rate. Methods and analysis We propose a study at the Affiliated Hospital of Shandong University of Chinese Medicine. A total of 90 individuals undergoing COH use a fixed GnRH antagonist protocol. They will be assigned randomly into two groups according to the trigger method and timing: recombinant hCG (6500 IU) will be injected only 36 hours before OPU for final oocyte maturation (hCG-only trigger); co-administration of GnRH-a and hCG for final oocyte maturation, 40 and 34 hours prior to OPU, respectively (Dual trigger). The primary outcome is metaphase-II (MII) oocytes rate. Secondary outcomes are number of oocytes retrieved, fertilization rate, top-quality embryos rate, blastula formation rate, embryo implantation rate, clinical pregnancy rate, miscarriage rate, live birth rate, cumulative pregnancy/live birth rates, and ovarian hyperstimulation syndrome (OHSS) rate. Ethics and dissemination The reproductive ethics committee of the Affiliated Hospital of Shandong University of Traditional Chinese Medicine certified this study (Identifier: SDUTCM/2021.7.26) as ethical. All individuals will sign written informed consent. All data and biological samples will be protected according to law. The results of this study will be disseminated in a peer-reviewed scientific journal. Registration details The study is registered at Chinese Clinical Trial Registry (ChiCTR). (chictr.gov.cn; ChiCTR2100049292)